Karakteristik Penderita Gagal Ginjal Kronik Yang Rawat Inap Di Rumah Sakit Umum Haji Medan Tahun 2012-2013 - Imelda Sari; Jemadi .; Hiswani . (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2014)
Chronic Renal Failure (CRF) is a failure of kidney function and metabolism to maintain fluid and electrolyte balance due to the progressive destruction of kidney structure. The report of Riskesdas 2013, the prevalence of CRF in Indonesia had been diagnosed by doctors 0,2%. To know the characteristic patients with CRF, conducted a research with a case series design in RSU Haji Medan. Population and sample was 180 people in 2012-2013 were recorded in hospital medical record. Univariate data were analyzed by descriptive while bivariate data were analyzed using Chi square test, Kruskal-Wallis test. The highest proportion of CRF patients in the age group 48-55 years (25,6%), Male (50,6%), Moslem (91,7%), Housewives (38,9%), come from Medan (69,4%), the main complaints of nausea + vomiting (38,3%), diseases history of Hypertension (28,3%), medical treatment of Medicine + Diet + HD (71,1%), average length of stay 7.22 days (7 days), clinical recovery out patient (76,1%), and Askes (35,0%). There was a significant difference between the proportion of age based medical management, the average long treatment by medical management.. There was no difference in the proportion of age by the state as home, the average long care by the state during the home. The writer suggest to improve the early detection and prevention of the disease CRF early age. The hospital is expected to complement a data-stage CRF patient on the status of the patient and insight into the diet to patients who have a history of hypertension and diabetes mellitus.